2003
DOI: 10.1111/j.1834-7819.2003.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic sequelae of dental erosion

Abstract: Background: The incidence of pulp involvement in patients with excessive wear has not been extensively documented. Methods: Clinical records of 448 patients with excessive tooth wear were reviewed and 52 cases (11.6 per cent) with near or frank pulp exposures or root canal treatments were found and their numbers and sites were tabulated. Light microscopy of study models was used to determine aetiology at each site of exposure as attrition, erosion or abrasion, scanning electron microscopy (SEM) was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
0
18
0
3
Order By: Relevance
“…Tooth erosion has attracted increasing attention in the dental community, as this is the most common form of wear in young people [Van Rijkom et al, 2002;Vargas- Ferreira et al, 2010]. It has been suggested that this oral condition is associated with discomfort, pain symptoms and altered aesthetics [Williams et al, 1999;Sivasithamparam et al, 2003;Wiegand et al, 2006] that could affect COHRQoL. However, traditional methods of measuring tooth erosion are quantitative and limited because they do not consider psychosocial and functional aspects of oral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tooth erosion has attracted increasing attention in the dental community, as this is the most common form of wear in young people [Van Rijkom et al, 2002;Vargas- Ferreira et al, 2010]. It has been suggested that this oral condition is associated with discomfort, pain symptoms and altered aesthetics [Williams et al, 1999;Sivasithamparam et al, 2003;Wiegand et al, 2006] that could affect COHRQoL. However, traditional methods of measuring tooth erosion are quantitative and limited because they do not consider psychosocial and functional aspects of oral health.…”
Section: Discussionmentioning
confidence: 99%
“…and pain symptoms [Williams et al, 1999;Sivasithamparam et al, 2003], dental sensitivity, enamel fracture and altered aesthetics [Kazoullis et al, 2007] that could affect the self-rating of oral health, perceived needs and quality of life. However, the majority of the studies have reported a low-severity grade of tooth erosion in children [Peres et al, 2005;Auad et al, 2007;Kazoullis et al, 2007;Correr et al, 2009;Mangueira et al, 2009].…”
mentioning
confidence: 99%
“…The prevalence of endodontic sequelae has not been systematically studied, but is estimated to occur in roughly 10% of patients with significant wear [8]. Pain, however, is not only induced by near or frank pulp exposure, but can occur as soon as dentine is exposed.…”
Section: Is Erosive Tooth Wear An Oral Disease?mentioning
confidence: 99%
“…The consequences of tooth wear are variable according to the literature. It has been suggested that tooth wear could affect the masticatory capacity and phonetics (40) , causing discomfort and pain symptoms (41,42) , dental sensitivity, enamel fracture and altered aesthetics (43) that could affect the self-rating of oral health, perceived needs and quality of life. However, the majority of studies have reported a low-severity grade of tooth erosion in children (43,(44)(45)(46)(47) .…”
Section: Discussionmentioning
confidence: 99%